REGIONAL VICE HEADS: POWER PLAYERS OR MERE PUPPETS? UNPACKING THE CONTRADICTIONS IN LAW NO. 23/2014 - Arifin, Firdaus (LITIGASI, 2024)
The role of the deputy regional head in Indonesia is primarily intended to complement the regional head by assisting in the execution of governmental duties. However, the ambiguity surrounding the deputy’s authority has emerged as a critical issue, often resulting in disharmony between regional heads and their deputies. If left unresolved, this tension may disrupt regional governance and prompt considerations of abolishing the deputy regional head position altogether. This study employs a normative juridical approach, analyzing secondary data through qualitative juridical methods to produce a descriptive narrative. The findings reveal that the regional head’s authority frequently overshadows the deputy’s role, rendering the deputy regional head largely symbolic and ineffective. This power imbalance has been a recurring source of conflict. To address this, the study proposes a Principle-Based Authorization Model to clearly define and strengthen the deputy’s authority, ensuring a more balanced and harmonious relationship. The urgency of this issue necessitates action from both the government and parliament to revise Law No. 23 of 2014 on Regional Government or to introduce specific regulations delineating the deputy’s responsibilities. By empowering the deputy regional head’s role, this reform could enhance the efficiency and effectiveness of regional governance, contributing to more stable and cooperative leadership at the regional level.